Running out of time - Haddix, Margaret Peter (New York Aladdin Paperbacks, 1997)
When a diphtheria epidemic hits her 1840 village, thirteen-year-old Jessie discovers it is actually a 1995 tourist site under unseen observation by heartless scientists, and it's up to Jessie to escape the village and save the lives of the dying children.
Braille.
76198
Keywords: Mystery and detective stories; Diphtheria -- Fiction; Indiana -- Fiction